CROSS-PLATFORM WEB DEVELOPMENT EXPLORING THE OFFLINE FUNCTIONS - Castro, Tiago Paiva (Revista Sinergia, 2018)
Besides the quality and productivity, in many cases cross-platform is a requirement in software development. Therefore, it is necessary to consider the differences and limitations between devices, not only mobile but non-mobile as well. Moreover, the software developer should deal with details about adequate behavior to technological evolution, like offline function and data synchronization with the server. There are a few solution to consider in cross-platform development available on the market, some of them being: cross-platform hybrid development and responsive web development. Among the solutions for cross-platform development the responsive web presents the highest range with the lowest cost. However, mobile devices do not have access to Internet at all times. To ensure the use of the software even without connectivity, it is important to consider functions that can operate offline. Therefore the project aims to evaluate and quantify the mechanisms for local data storage and synchronization with the server to allow the use of web software in places without Internet connection.